Regulation of Sacha Inchi protein on fecal metabolism and intestinal microorganisms in mice - Wu, Kuan; Gong, Wanying; Lin, Shiyang; Huang, Si; Mu, Hongyu; Wang, Mingming; Sheng, Jun; Zhao, Cunchao (Frontiers in Nutrition, 2024)
Sacha Inchi Protein (SIP) is a high-quality plant protein extracted from Sacha Inchi meal. This study aimed to investigate the impact of SIP on mouse metabolomics and gut microbiota diversity and explore the underlying pathways responsible for its health benefits. In this study, the structural composition of SIP was investigated, and the effects of SIP on fecal metabolomics and intestinal microorganisms in mice were explored by LC-MS metabolomics technology analysis and 16S rRNA gene sequencing. The results showed that SIP was rich in amino acids, with the highest Manuscript Click here to view linked References content of arginine, which accounted for 22.98% of the total amino acid content; the potential fecal metabolites of mice in the SIP group involved lipid metabolism, sphingolipid metabolism, arginine biosynthesis, and amino acid metabolism; SIP altered the microbial composition of the cecum in mice, decreased the Firmicutes/Bacteroidetes value, and It decreased the abundance of the harmful intestinal bacteria Actinobacteriota and Desulfobacterota, and increased the abundance of the beneficial intestinal bacteria Faecalibaculum, Dubosiella. In conclusion, SIP is a high-quality plant protein with great potential for development in lipid-lowering, intestinal health, and mental illness, providing valuable clues for further research on its health-promoting mechanisms.